Standardization of Jala Peenisa Choornam Used for Peenisa Rogam - Madushani, Y.M.P.K.; Sulosana, P.; Selvaluxmy, K.; Medawatta, H.M.U.I.; Thayalini, T. (Asian Journal of Medicine and Health, 2017)
Indigenous Medicine of Sri Lanka consists of Ayurveda, Siddha and Unani Medicines. Herbal drugs are commonly used in Siddha Medicine. Peenisa Rogam is one of the common diseases of neck and above. Jala Peenisa choornam (JPC) mentioned in Siddha literature for the treatment of Jaladosham (Acute rhinitis) contains powder of Caesalpinia bonducella seeds, Curciuma longa rhizome and Nigella sativa seeds in 2:1:1 w/w ratio. There is no validated scientific data on the efficacy of JPC on Peenisa Rogam. Therefore, this study was aimed to standardize the JPC in terms of phytochemicals, physico-chemicals and antioxidants as total polyphenolic content (TPC) before evaluating the efficacy. C. bonducella seeds, C. longa rhizome and N. sativa seeds were cleaned, dried, powdered separately and blend together in 2:1:1 w/w ratio to obtain JPC and used for the standardization. TPC was determined by Folin-Ciocalteu method. The results revealed that the physico-chemical parameters: moisture, total ash, acid-insoluble ash, water soluble ash, water extractable matter and ethanol extractable matter are 2%, 4.98±0.001%,
Keywords: Standardization; Jala Peenisa choornam; Peenisa Rogam